Enhancing Reliability and Maintenance Efficiency of Screw Press Machines in Palm Fruitlet Processing Mills: A Failure Mode and Effect Analysis (FEMA) Approach - Aditya, Abbiyu Bima; Nugroho, Bagus; Hermantoro, Hermantoro; Renjani, Rengga Arnalis (Akademi Komunitas Perkebunan Yogyakarta, 2025)
This study analyzed the reliability and failure risks of screw press machine components in a palm oil loose fruit mill using the Failure Mode and Effect Analysis (FMEA) method. The objective was to identify critical components, evaluate their Risk Priority Number (RPN), and propose appropriate maintenance strategies. Data were collected through questionnaires, field observations, and maintenance records. The RPN was calculated by multiplying severity, occurrence, and detection scores, while reliability was assessed using the Mean Time Between Failures (MTBF) formula. The worm screw showed the highest RPN at 252, indicating a critical risk level, while the press cage followed with an RPN of 210. MTBF analysis revealed that the worm screw required replacement every 313.5 hours, whereas components like the V-belt and electro motor had longer MTBF intervals of up to 3135 hours. The findings suggested that targeted maintenance on high-risk components could reduce downtime and enhance production efficiency. This study concluded that prioritizing preventive maintenance based on RPN and MTBF results was crucial for maintaining the operational performance of screw press machines in palm oil processing.